Early detection of skin cancer in Australia - current approaches and new opportunities - Monika Janda; Catherine M Olsen; Victoria J Mar |; Anne E Cust (Sax Institute, 2022)
Objectives and importance of study: Melanoma and keratinocyte carcinomas impose a significant health and financial burden on the Australian population and healthcare system. The impacts of skin cancer can be minimised through early detection, as morbidity, mortality and costs of treatment are strongly associated with stage of disease at diagnosis. Study type: Narrative review. Methods: Building on the discussions from the Melanoma Screening Summit held in Brisbane, Australia, in 2019, we reviewed evidence related to current approaches and new opportunities for early detection of melanoma and other skin cancers. Results: Population-based melanoma screening is not currently recommended due to insufficient evidence that screening reduces melanoma mortality. Instead, in most countries including Australia, early detection of melanoma and keratinocyte carcinomas is undertaken opportunistically, by either the patient presenting for a routine skin check or with a lesion of concern, or by the doctor detecting a lesion incidentally. Several concerns about the current unstructured approach to skin cancer early detection have been identified, including variable quality of care, sociodemographic inequalities in medical access and health outcomes, excision of many benign lesions, overdiagnosis, gaps in workforce training, and health system inefficiencies. There has also been renewed interest in melanoma screening in Australia, driven by a changing landscape of skin cancer early detection. These changes include increasing health system costs for adjuvant therapies, advances in diagnostic technologies and artificial intelligence, the availability of validated risk-stratification tools, and consumer-driven digital technologies. Conclusions: The future of skin cancer early detection in Australia and internationally may incorporate features such as a more structured approach to skin cancer risk assessment using online risk calculators and invitations to screen, consumer-driven melanoma surveillance, and new technologies for diagnosis and monitoring of lesions. High-quality research evidence is being generated across multiple research programs, and is essential to underpin any changes to policy and practice in skin cancer early detection.